Incontinence-associated dermatitis in elderly patients: prevalence and risk factors - Ferreira, Mariana [UNESP]; Abbade, Luciana [UNESP]; Mangini Bocchi, Silvia Cristina [UNESP]; Miot, Helio Amante [UNESP]; Boas, Paulo Villas [UNESP]; Carvalho Passos Guimaraes, Heloisa Quatrini (Assoc Brasileira Enfermagem, 2020)
Objective:To determine the prevalence and risk factors for incontinence-associated dermatitis in the elderly. Method: Cross-sectional exploratory study carried out in public hospitals. The dermatitis prevalence and associations were obtained by calculating the ratio. The effect dimension was estimated by the odds ratio with a 95% confidence interval and statistical significance p <0.05. Results: 138 elderly people were included, with an average age of 77.2 years old (+/- 9.3); 69 (50%) had combined fecal and urinary incontinence. The dermatitis prevalence was 36.2% (50); 28% (14) had pressure injuries; 14% (7), candidiasis. Risk factors were: longer hospital stay (Odds Ratio = 5.8 [2.6-12.9]), obesity (Odds Ratio = 3.6 [1.2-10.4]), high level of dependence (Odds Ratio = 2.4 [1,1-5,0]) and high risk for pressure injury (Odds Ratio = 6.1 [1,4-26,9]). Conclusion: The study found a high prevalence of dermatitis associated with incontinence. The early recognition of risk factors favors effective preventive actions.
Keywords: Dermatitis; Diaper Rashes; Aged; Prevalence; Risk Factors